The Effect of Show and Tell Method on Students’ Speaking Descriptive Text Ability - Santiur Maida Hutagalung; Gabby Maureen Pricilia; Habib Rahmansyah (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2026)
The primary objective of this inquiry was to evaluate how the Show and Tell Method influences the descriptive oral performance of eighth-graders at SMP Negeri 3 Sibabangun. Methodologically, the investigation framed its data collection within a quantitative, pre-experimental framework, specifically employing a single-group pre-test and post-test arrangement. The entire sample, comprising 28 students, was selected via a total sampling technique. To gather the necessary data, the researcher employed speaking tests and observation sheets. Based on classroom observations, the execution of the Show and Tell Method successfully secured an 80% score, the observation results reached a score that was categorized as “Good.” The students’ mean score increased from 45 in the pre-test to 70 in the post-test. In addition, based on the Wilcoxon Signed Rank Test, the calculated W value (391) was higher than the critical W value (116) at the 5% significance level. This result indicated a statistically significant improvement in the students’ ability to speak descriptive texts after the implementation of the Show and Tell Method. Consequently, the alternative hypothesis (Ha) was accepted, while the null hypothesis (H₀) was rejected. Therefore, the Show and Tell Method was proven to have a significant effect on students’ descriptive text speaking skills and enhanced their oral performance through object presentation and descriptive activities.